2013
DOI: 10.1111/gbb.12025
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila social clustering is disrupted by anesthetics and in narrow abdomen ion channel mutants

Abstract: Members of many species tend to congregate, a behavioral strategy known as local enhancement. Selective advantages of local enhancement range from efficient use of resources to defense from predators. While previous studies have examined many types of social behavior in fruit flies, few have specifically investigated local enhancement. Resource-independent local enhancement has recently been described in the fruit fly using a measure called social space index, although the neural mechanisms remain unknown. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 66 publications
3
30
0
Order By: Relevance
“…Thus, interaction between flies follows a non-random pattern [77]. In our study, inter-fly distance was used as a measure for social interaction [52,53,78,79], and we found that when the flies exposed to BPA were placed in a social setting, there was a decrease in the inter-fly distance. This decrease may be due to aberrant social interaction, in which the flies do not maintain the ideal balance of attraction/repulsion and interact inappropriately with each other.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Thus, interaction between flies follows a non-random pattern [77]. In our study, inter-fly distance was used as a measure for social interaction [52,53,78,79], and we found that when the flies exposed to BPA were placed in a social setting, there was a decrease in the inter-fly distance. This decrease may be due to aberrant social interaction, in which the flies do not maintain the ideal balance of attraction/repulsion and interact inappropriately with each other.…”
Section: Discussionmentioning
confidence: 55%
“…The distance between an individual fly and its closest neighboring flies was used as a measure of social interaction within the group, as previously described [50,52,53]. In a social setting, most Canton-S wild-type flies maintain at least a two body length distance from their closest neighbor (∼0.25 cm) [54].…”
Section: Abnormal Social Interactions In Drosophila Following Bpa Expmentioning
confidence: 99%
“…We first tested the ability of the flies to avoid the Drosophila stress odorant (dSO) left by agitated flies in the avoidance assay (Suh et al, 2004; Fernandez et al, 2014). We also tested the flies’ response to others in social clustering, the measure of distances to their closest neighbor (their social space), in a stable undisturbed group (Burg et al, 2013; Simon et al, 2012). Social space and social avoidance probably result from equilibrium between multiple attractive and repulsive cues (reviewed in Mogilner et al, 2003), in addition to environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…This time delay does not affect social space in CS flies (Simon et al, 2012). Digital images were imported in ImageJ software (NIH, rsbweb.nih.gov/ij) and analyzed for nearest neighbor distances as described in (Burg et al, 2013). These data were imported into GraphPad Prism 6 for further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation